2022
DOI: 10.2147/ijgm.s356476
|View full text |Cite
|
Sign up to set email alerts
|

Diet-Related Inflammation is Associated with Malnutrition-Inflammation Markers in Maintenance Hemodialysis Patients: Results of a Cross-Sectional Study in China Using Dietary Inflammatory Index

Abstract: Purpose This cross-sectional study aimed to explore the association between the inflammation potential of the diet and malnutrition-inflammation status in Chinese maintenance hemodialysis (MHD) patients. Methods Dietary Inflammatory Index (DII) was computed based on a semi-quantitative food frequency questionnaire. Malnutrition-inflammation status was assessed by six indexes, including C-reactive protein (CRP), neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…In a crosssectional study of 109 HD patients, Kizil et al demonstrated that an increase in the DII category was associated with higher CRP levels (15). Similarly, another cross-sectional study with 160 HD patients reported a signi cant positive association between the DII score and CRP levels (14). Other studies conducted among different populations have also shown signi cant associations between DII and in ammatory biomarkers effective in CKD-aP, such as interleukin-6, interleukin-2, and tumor necrosis factor-α(36).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In a crosssectional study of 109 HD patients, Kizil et al demonstrated that an increase in the DII category was associated with higher CRP levels (15). Similarly, another cross-sectional study with 160 HD patients reported a signi cant positive association between the DII score and CRP levels (14). Other studies conducted among different populations have also shown signi cant associations between DII and in ammatory biomarkers effective in CKD-aP, such as interleukin-6, interleukin-2, and tumor necrosis factor-α(36).…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have demonstrated the direct correlation between DII scores and chronic diseases such as chronic kidney disease (10), obesity (11), diabetes mellitus (12), and cardiometabolic risk (13). Furthermore, several cross-sectional studies have reported a positive correlation between DII scores and CRP levels in hemodialysis patients (14,15).…”
Section: Introductionmentioning
confidence: 98%
“…Previous study showed that using 28 components did not influence the DII predictive capacity [ 24 ]. Details of the DII scoring algorithm have been described previously [ 19 ]. First, global daily mean intake was adopted to calculate every participant’s Z score.…”
Section: Methodsmentioning
confidence: 99%
“…Instead of focused on specific nutrients or dietary patterns, dietary inflammatory index (DII), a literature-based scoring algorithm based on the effort of 45 different food components on inflammatory biomarkers, was focused on quantitating the overall inflammatory potential of individual diets [16]. A higher DII score was independently linked with obese, malnutrition-inflammation status and cardiovascular disease [17][18][19].…”
Section: Introductionmentioning
confidence: 99%